SECTION 61 OF THE TRUSTEE ACT 1925: A JUDICIOUS BREACH OF TRUST?. (7th September 2017) - Haley, Michael
Abstract: This article is concerned with s. 61 of the Trustee Act 1925. It will analyse the origins, design and modern day operation of the jurisdiction to relieve a trustee from personal liability following a breach of trust. It will revisit the threshold conditions of honesty, reasonableness and fairness and, in the context of mortgage fraud, contend that this exculpatory jurisdiction ought not extend to the bare commercial trust that exists between the mortgagee and its solicitor. Defects, uncertainties and shortcomings associated with s. 61 will also be addressed.